Cranial morphological variation among contemporary Mexicans: Regional trends, ancestral affinities, and genetic comparisons. Issue 4 (11th June 2013) - Hughes, Cris E.; Tise, Meredith L.; Trammell, Lindsay H.; Anderson, Bruce E.
ABSTRACT Genetic research has documented geographical variation within Mexico that corresponds to trends in ancestry admixture from postcolonial times on. The purpose of this study is to determine whether craniometric variation among contemporary Mexicans is comparable to that reported in genetic studies. Standard osteometric measurements were taken on 82 male crania derived from forensic cases, with geographic origins of the specimens spanning over two‐thirds of Mexico's states. To study similarities in regional clustering patterns with genetic data, k‐means clustering analyses were performed, followed by chi‐square tests of association between cluster assignments and geographic region of origin. Normal mixtures analyses were performed, centered on three "ancestral" sample proxies to estimate classification probability to each ancestry. The results demonstrate that the cranial morphological sample data cluster similarly to the regional groupings inferred from the genetic data. Additionally, the results indicate a gradient trend in population structure for contemporary Mexicans, with the proportion of Amerindian ancestry increasing from North to South while, conversely, European ancestry proportion estimates increase from South to North. Furthermore, the probabilities for classification of African ancestry remained low across the regions, again reflecting the results for the genetic data. Cranial morphological variation is well aligned with the genetic data for describing broad trends among Mexican populations, as well as yielding comparable estimates of general ancestry affiliations that reflect Mexico's history of Spanish contact and colonialism. Am J Phys Anthropol 151:506–517, 2013. © 2013 Wiley Periodicals, Inc.